Towards Methodology for User Experience Measurement in On-Line Services - Sikorski, Marcin; Garnik, Igor (Rozwój metodyki pomiaru jakości odczuwanej usług on-line, 2010)
This paper presents results of a user-based study, aimed at identification and assessment of non-technological factors shaping long-term user satisfaction in on-line services as well as prospective customer loyalty. The study has shown that attractive price appears to be critical to customer, next feeling of security and of being well informed. Next, convenience in using the service in terms of time and workload have been declared by users as of secondary importance. By showing the significance of non-technological factors “beyond usability” the study contributed to methodological development in research on user-perceived quality of on-line services.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 147, s. 244-254
Keywords: user-centred design; on-line services; on-line consumer behaviour